1998
DOI: 10.1046/j.1365-2559.1998.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal‐storing histiocytosis and immunocytoma associated with multifocal fibrosclerosis

Abstract: This case is, to the authors' knowledge, the first to be described in which crystal-storing histiocytosis is associated with a clinical picture of multifocal fibrosclerosis, which suggests that lymphoproliferative processes should be considered in the differential diagnosis of the various conditions associated with multifocal fibrosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…Fewer cases have been seen with benign plasmacytosis, as localized tumours in organs such as stomach and in association with multifocal fi brosclerosis [2,3]. The majority of reported cases of plasma cell dyscrasia accompanied by crystal storing histiocytosis had kappa chain as the monoclonal light chain.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer cases have been seen with benign plasmacytosis, as localized tumours in organs such as stomach and in association with multifocal fi brosclerosis [2,3]. The majority of reported cases of plasma cell dyscrasia accompanied by crystal storing histiocytosis had kappa chain as the monoclonal light chain.…”
Section: Discussionmentioning
confidence: 99%
“…8 Non-neoplastic conditions occasionally associated with CSH include rheumatoid arthritis 3 and amyloidosis. 9 The current case illustrates the utility of fine-needle aspiration for detection of CSH, leading to discovery of MGUS. Review of the literature revealed only one published case of CSH diagnosed by fine-needle aspiration of the parotid gland 2 and the current case represents the first published case of CSH diagnosed by fine-needle aspiration of the lung, to our knowledge.…”
Section: Discussionmentioning
confidence: 86%
“…CSH is an uncommon phenomenon that is usually seen in disorders associated with the expression of monoclonal Ig [1,2,3,4,5,6,7,8,9] and only rarely in nonneoplastic conditions [11,12,13]. CSH associated with extranodal MZL or mucosa-associated lymphoid tissue lymphoma has been reported in a few cases, with the location of the MZL being the parotid gland [22], ocular adnexa [23], lacrimal gland [20], and lung [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…It has frequently been described in association with B cell neoplasms, such as multiple myeloma [1,2,3,4,5], monoclonal gammopathy of undetermined significance [6], lymphoplasmacytic lymphoma [7,8,9] and other low-grade B cell lymphoproliferative disorders [10]. It has also been described in some nonneoplastic conditions [11,12,13], including rheumatoid arthritis [11], amyloidosis [12], and histiocytic accumulations of phagocytosed clofazimine, a drug used to treat lepromatous leprosy [14,15,16]. Furthermore, CSH can occasionally precede a diagnosis of malignancy [1].…”
Section: Introductionmentioning
confidence: 99%